Transfusion practice in Australia: an internet‐based survey. Issue 4 (13th January 2021) - Poh, D; Claus, M; Smart, L; Sharp, CR
Abstract : Objective: To describe small animal transfusion practices in Australia, including access to blood products and frequency of pre‐transfusion compatibility testing and medication administration. Methods: An online survey was disseminated to target Australian veterinarians treating dogs and cats. Information collected included demographics, sources of blood products, blood storage, recipient compatibility testing and administration of medications pre‐transfusion. Associations between the use of compatibility tests and premedications were assessed using the χ 2 test. Significance was set at P < 0.05. Results: A total of 199 Australian veterinarians were included; however, there was some attrition of respondents over the course of the survey. The majority of respondents were in general practice (n = 133/199). Access to fresh whole blood was commonly reported for dogs (n = 179/199) and cats (n = 131/198), whereas blood components were less commonly available (canine red blood cells [RBC], n = 52/199 and plasma, n = 157/199; feline RBC, n = 9/198 and plasma, n = 21/198). Most blood was sourced from the pets of owners affiliated with the veterinary clinic (n = 179/196). The respondents who did not blood type or crossmatch dogs were significantly more likely to use premedication than those who did these tests (both comparisons: P < 0.001). Likewise, the respondents who did not blood‐type cats were significantly more likely to use premedication (P = 0.003); however, there was no association between crossmatching and using premedication in cats (P = 0.183). Conclusion: This is the first survey to describe transfusion practices across a variety of practice types throughout Australia. Future work is needed to determine how representative these results are of current transfusion practices across Australia, and if so, what can be done to optimise them.